“ASSESSMENT OF HYPOGLYCEMIC CONDITIONS IN PATIENTS WITH TYPE 1 AND TYPE 2 DIABETES MELLITUS USING A QUESTIONNAIRECSP-DM-HYPOGL (COMPREHENSIVE SYMPTOM PROFILE-DIABETES MELLITUS HYPOGLYCEMIA MODULE)" (World Bulletin of Public Health, 2024)
to study the value of the CSP-DM-HypoGl (Comprehensive Symptom Profile-Diabetes Mellitus Hypoglycemia Module) questionnaire in patients with type 1 and type 2 diabetes mellitus according to negotiability data